HUKUM SEBAGAI PILAR PERLINDUNGAN HAK KODRAT: TELAAH TEORI JOHN LOCKE DALAM SISTEM HUKUM MODERN - Pikulun , Selfario Adhityawan; Seftian, Baiq Vara Arisinda (Al-Muqaronah: Jurnal Perbandingan Mazhab dan Hukum, 2024)
John Locke's natural rights theory asserts that individuals are inherently endowed with the right to life, liberty, and property from birth. According to Locke, the law serves as a mechanism to safeguard these rights from violations by the state or other individuals. This study aims to explore the concept of natural rights in Locke's theory, its influence on the protection of human rights in democratic systems, and the challenges faced in its modern application. Findings reveal that Locke's ideas have laid the groundwork for numerous constitutions and international human rights documents, such as the Universal Declaration of Human Rights. However, challenges in implementation include social and economic inequality, globalization, and conflicts between individual freedoms and state interests. Thus, the protection of natural rights remains pivotal as a foundation for justice and the respect of human rights in contemporary legal systems.